Innovation of Public Services by Population and Civil Service of Pasaman District - Oktarizal Vandhika; Roni Ekha Putera; Desna Aromatica (Adabi : Journal of Public Administration and Business, 2024)
The purpose of this study is to describe the implementation of public service innovations carried out by Disdukcapil Pasaman Regency. This type of research is qualitative by describing the form of implementation of public service innovation by Disdukcapil Pasaman Regency. Innovation is the creation and implementation of new processes, products, services and methods that can produce quality improvements that are effective and efficient. However, innovation can also be in the form of expansion or improvement of existing services, so as to create better service than before. Public Service Innovation is an increase in population administration services by making these services accessible anywhere and anytime by the public.